Food and feeding habits of white-throated kingfisher (Halcyon smyrnensis) in Bangladesh (Bangladesh Journal of Zoology, 2015)
Food items, preying and feeding activities of white-breasted Kingfisher, Halcyon smyrnensis were studied from September 2008 to September 2011 at Nikunja-1 in Dhaka City Corporation area. A total of 16 species of food items were recorded from the observation. Fishes (more than 60%) were mostly preferred item. The highest preference was fry of Labeo rohita (30.6%). They highly preferred the species belonging to the Family Cyprinidae and Order Cypriniformes. The length of the food items varied from 2.0 to 12.3 cm. Surface dweller species (85.8%) was highly preferred. During preying, they used 0.3 to 2.25 m height, among which the highest preference was 0.9 m (32%). H. smyrnensis targeted the food items before catching while they took 9 sec to 15 min 17 sec. After catching they either engulfed the prey immediately or hold it at their beak for 2 sec to 30 min 30 sec before engulfing. Bamboos found in the water body were mostly preferred (65.9%) as perching places during preying.Bangladesh J. Zool. 42(2): 237-249, 2014